2003
DOI: 10.1107/s0108270103008679
|View full text |Cite
|
Sign up to set email alerts
|

1-(2-Hydroxy-4-methoxyphenyl)-3-(2,3,4-trimethoxyphenyl)prop-2-en-1-one

Abstract: The title compound, C(19)H(20)O(6), crystallizes in the centrosymmetric space group P2(1)/c with one molecule in the asymmetric unit. The molecule is approximately planar and the dihedral angle between the phenyl rings is 11.0 (1) degrees. The H atoms of the central propenone group are trans. There is an intramolecular O-H.O hydrogen bond and the molecules are crosslinked by four intermolecular C-H.O hydrogen bonds, producing a three-dimensional network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…On the other hand, the distance between 36O···42O of the prenyl chain and the methoxy group attached to B-ring is 2.766 Å, which determines directly the orientation for methoxy groups. This correlates quite well with the results obtained by the X-Ray diffraction studies reported for similar structures [6]. …”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…On the other hand, the distance between 36O···42O of the prenyl chain and the methoxy group attached to B-ring is 2.766 Å, which determines directly the orientation for methoxy groups. This correlates quite well with the results obtained by the X-Ray diffraction studies reported for similar structures [6]. …”
Section: Resultssupporting
confidence: 92%
“…As observed in Table 2, the corresponding geometrical parameters for chalcones 4 [6], 5 [38], 6 [39] and 7 [5] obtained by X-ray diffraction show similar values even though the molecules have different substituents in their structure (See Figure 1). This could indicate that the introduction of diverse functional groups into the aromatic ring system has little effect on specific geometrical parameters (prop-2-en-1-one chain), as reported in previous theoretical and experimental studies [40].…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations